The Effects of Interspecific Courtship on the Mating Success of Aedes aegypti and Aedes albopictus (Diptera: Culicidae) Males. (5th May 2015) - Bargielowski, Irka; Blosser, Erik; Lounibos, L. P.
Abstract : Satyrization, a form of asymmetric reproductive interference, has recently been shown to play a role in competitive displacements of Aedes aegypti (L.) by Aedes albopictus (Skuse). Furthermore, female Ae. aegypti from populations in sympatry with Ae. albopictus have evolved reproductive character displacement and changes in mating behavior to reduce interspecific mating . In this article, we examine evolutionary responses of males to interspecific mating and show that satyrization has also evoked reproductive character displacement in males. We demonstrate that the presence of heterospecific females negatively influences conspecific mating success in male Ae. aegypti, most likely due to misdirected courting or mating efforts, and that males of this species from populations in sympatry with Ae. albopictus have evolved to be less influenced by the presence of heterospecific females than their allopatric counterparts. Conversely, we suggest that the presence of conspecifics may, in some circumstances, increase interspecific mating. This study demonstrates that co-occurrences of these two invasive species may lead to evolution and adaptation of reproductive behaviors to changing circumstances. Understanding the processes driving development of mate choice preferences or avoidance mechanisms may help predict future changes in the distribution and abundance of insect vectors or pests.